Experimental Investigation Of RB-SiC Using Cu–CNF Composite Electrodes In Electrical Discharge Machining - Liew, Pay Jun; Zainal, Nurlishafiqa; Ahsan, Qumrul; Zhou, T.; Yan, J. (Springer-Verlag London Ltd, 2018)
The performances of carbon nanofiber (CNF) reinforced copper (Cu) composite electrodes on the reaction-bonded silicon carbide (RB-SiC) ceramic were experimentally investigated by using electrical discharge machining (EDM). The effects of CNF content on material removal rate (MRR), electrode wear ratio (EWR), surface roughness (SR) and surface topography were examined. Results indicated that the addition of CNF to the Cu electrode increased the MRR of the workpiece. In addition, increasing the added CNF content increased the EWR of the Cu–CNF composite electrode and the SR of the machined surface. The results of one-way ANOVA indicated that the Cu–1.0 wt% CNF composite electrode exhibited the optimal MRR and EWR values, although this electrode resulted the maximum SR on the RB-SiC machined surface.